Current Understanding of the Regulatory Mechanism of Tooth Root Development and Future Perspectives - Natalie Black; Yang Chai (Taylor & Francis Group, 2023)
ABSTRACTBackground The purpose of this review article is to understand tooth root development and its regulation through evolution and epigenetics as well as future implications involving root regeneration and tissue engineering.Types of Studies Reviewed We performed a comprehensive PubMed search to review all published studies related to the molecular regulation of tooth root development and regeneration until August 2022. Articles selected include original research studies and reviews.Results Epigenetic regulation strongly influences dental tooth root patterning and development. One study highlights how genes such as Ezh2 and Arid1a are crucial components in the development of tooth root furcation patterning. Another study shows that loss of Arid1a ultimately leads to shortened root morphology. Furthermore, researchers are utilizing information about root development and stem cells to find alternative treatments in replacing missing teeth through a stem cell-mediated bioengineered tooth root (bio-root).Practical Implications Dentistry values preserving natural tooth morphology. Presently, implants are the best treatment for replacing missing teeth, but alternative future treatments might include tissue engineering/bio-root regeneration to restore our dentition.